The Influence of Referral Marketing and Customer Trust on Purchasing Decisions Through Customer Satisfaction at PT. Dharma Lautan Utama Surabaya - Kartika, Chandra; Dandy, Firman; Soenarmi, Soenarmi (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: This research is entitled "The Influence of Referral Marketing and Customer Trust on Purchasing Decisions through Customer Satisfaction at PT. Dharma Lautan Utama Surabaya". The purpose of this study is to describe referral marketing, customer trust, purchase decisions and customer satisfaction in the company, as well as to determine and analyze the influence of referral marketing and customer trust on purchasing decisions both directly and through customer satisfaction. This research is an explanatory research with a quantitative approach. Design/Methodology/Approach: The population in this study is customers who are already customers of sea transportation companies and ferry crossings at PT. Dharma Lautan Utama Surabaya. The number of samples taken in this study was as many as 100 respondents from customers who had subscribed to the Marine Transportation Company and ferry crossings PT. Dharma Lautan Utama Surabaya is more than one year old and uses saturated sampling. Data collection was carried out using the questionnaire dissemination method. The variables studied in this study are purchasing decision as a dependent variable, referral marketing and customer trust as independent variables, and customer satisfaction as an intervening variable. The data analysis technique is SEM using Partical Least Square (PLS). Findings: The results of the analysis show that referral marketing has a positive and significant effect on customer satisfaction. Customer trust has a positive and significant effect on customer satisfaction. Referral marketing has a positive and significant influence on purchasing decisions. Customer trust has a positive and insignificant effect on purchasing decisions. Customer satisfaction has a positive and significant effect on purchasing decisions. Referral marketing has a positive and significant influence on purchasing decisions through customer satisfaction. Customer trust has a positive and significant influence on purchasing decisions through customer satisfaction. Paper Type: Research Paper